UPGRADING KATALITIK DISTILAT MINYAK BATUBARA BANKO SELATAN DENGAN KATALIS NIMO SULFIDA - Murti, Sri Djangkung Sumbogo; Hartiniati, Hartiniati (Jurnal Energi dan Lingkungan (Enerlink), 2008)
Catalytic hydrotreatment of South Banko coal liquid (SBCL) middle distillate (b.p.300 ? 420 oC) was performed over NiMo sulfides catalysts. The hydrotreatmentwas conducted in an autoclave of 50 ml capacity under the conditions of 340 ?420 oC, 60 and 120 min and initial hydrogen pressure of 5 ? 10 MPa. Thehydrotreatment reduced the contents of all heteroatom species (S, N and O).Sulfur species were easiest to be removed, while nitrogen species were mostrefractory. Reactivities of some representative heteroatom species weremeasured to find the refractory species in coal liquid by GC-AED. Carbonsupported catalyst was compared to alumina supported one confirming its higheractivity for hydrodesulfurization, hydrodenitrogenation and hydrodeoxygenation.Kata kunci: coal liquid, middle distillate, Katalis NiMo, hydrotreatment,heteroatom, GC-AED, hidrodesulfurisasi, hidrodeoksigenasi,hidrodenitrogenasi